Electric System Design of 3 000 HP Energy-saving and Environment-friendly Shunting Diesel Locomotive - Jibin WEN; Jinglai LIU; Hong WEI; Fei DONG; Mingyan WANG; Yue DENG (机车电传动)
The design background of 3 000 HP energy-saving and enviroment-friendly shunting diesel locomotive was introduced. Configuration, main technical parameters and expected traction and braking performance requirements of the locomotive were briefly described. The main drive system, auxiliary drive system, power battery management system and locomotive control system were mainly introduced. The working principles, system components and parameters of the main components of the system were introduced. Finally, the locomotive commissioning and test conditions were described. The test proved that the electric system was stable and reliable, with excellent performance.